Expansion, characterisation and differentiation of human neural stem cells - Ye, Yee May (Universiti Sains Malaysia, 2015)
Stroke irreversibly damages affected brain part, leading to permanent neuronal impairment. Neural stem cell (NSC)-based therapy is a potential stroke treatment due to its ability to self-renew and to differentiate into various viable neuronal cells for damaged brain tissue regeneration. Here, human NSCs were expanded from GIBCO® human NSC line and stroke patients’ brain subventricular zone (SVZ) tissue biopsy with ethical approval. NSCs obtained from GIBCO® cell line were used for pilot testing of NSC characterisation and differentiation ability in vitro. GIBCO® NSCs were cultured in complete StemPro®NSC SFM while human brain SVZ tissues were cultured in an adherent layer with serum-free medium containing bFGF and EGF. Characterisation of NSC was performed using qRT-PCR and Western blot; while NSC differentiation was performed using Neuron Differentiation Medium and Astrocytes Differentiation Medium. Both assays used human normal brain cell line (SVG-pl2) as negative control. qRT-PCR data illustrated that NSCs showed over 4000-fold difference in Nestin and 6000-fold difference in CD133 expression compared to SVG-pl2, indicated that Nestin and CD 133 were specific to NSC. These results were consistent with the Western blot data in which Nestin protein with approximately 200 kDa was identified in NSCs but was absent in SVG-pl2. Upon four days in culture with differentiation media, NSCs did not show morphological changes towards neurons and astrocytes respectively, compared to non-treated cells. This is due to the limited time available to perform this assay in present study. Longer culture duration which is more than one week will be performed in future to obtain more accurate result. Meanwhile, two clonal neurospheres were obtained from SVZ tissue culture, indicated that the